STRATEGI BISNIS RITEL TRADISIONAL DI TENGAH PERSAINGAN BISNIS MINI MARKET MODEREN (Fokus Ekonomi, 2010)
This study explores and measures several factors in terms of the business traditional retails’ strengths, weaknesses, opportunites and threaths, using Factor Analysis. These all factors are used to determine competitive advantage strategy alternatives using SWOT Analysis. Unit Analysis used in this study is the individual subjects, taken from the small-unstrutured stores (warung tradisional) and traditional markets, and modern retails (modern minimarkets).  The results show that there are many weakneses and threaths factors facing the traditional retails as the determined factors for formulating the competitive advantage strategy, compared to modern retails having the many strengths factors. The main formulated various competitive advantage strategies for tradional retails in oder to compete with the modern retails are as follows:1) improving product quality assurance; 2) implementing infrastructure management to get comportable, and safety store atmosphere; 3) focusing on innovatif services and offering certain or special products. These strategies are the uniqness strategy for sustainning the traditional retails toward the retail business competitiveness. These unique developed strategies are formulated based on generic strategy by Jauch and Glueck (1997), and Porter (1995), in term of focus and retrenchment strategy